Transient fault tolerant control for vehicle brake-by-wire systems. (May 2016) - Huang, Shuang; Zhou, Chunjie; Yang, Lili; Qin, Yuanqing; Huang, Xiongfeng; Hu, Bowen
Abstract: Brake-by-wire (BBW) systems that have no mechanical linkage between the brake pedal and the brake mechanism are expected to improve vehicle safety through better braking capability. However, transient faults in BBW systems can cause dangerous driving situations. Most existing research in this area focuses on the brake control mechanism, but very few studies try to solve the problem associated with transient fault propagation and evolution in the brake control system hierarchy. In this paper, a hierarchical transient fault tolerant scheme with embedded intelligence and resilient coordination for BBW system is proposed based on the analysis of transient fault propagation characteristics. In this scheme, most transient faults are tackled rapidly by a signature-based detection method at the node level, and the remaining transient faults, which cannot be detected directly at the node level and could degrade the system performance through fault propagation and evolution, are detected and recovered through function and structure models at the system level. To jointly accommodate these BBW transient faults at the system level, a sliding mode control algorithm and a task reallocation strategy are designed. A simulation platform based on Architecture Analysis and Design Language (AADL) is established to evaluate the task reallocation strategy, and a hardware-in-the-loop simulation is carried out to validate the proposed scheme systematically. Experimental results show the effectiveness of this new approach to BBW systems. Highlights: We propose a hierarchical transient fault tolerant scheme for BBW systems. A sliding mode algorithm and a task strategy are designed to tackle transient fault. The effectiveness of the scheme is verified in both simulation and HIL environments.